Analisis Tingkat Resiko Kecelakaan Kerja pada Galangan Kapal Logistik di PT X dengan Metode HIRARC - Akbar, Anshari; Mangka, Andi; Andivas, Marulan (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Logistics companies are very important in managing materials for smooth operations. In this company, which specializes in logistics through ocean shipping, faces risks when carrying out tasks such as lifting logistics goods in containers, moving oil, coal, and machine tools. To minimize the possibility of accidents, is necessary to identify, analyze, and manage potential hazards using the HIRARC method. Risk assessment shows variations in risk levels for different activities and control efforts. Hazard control is carried out through measures such as being exposed to embers that cause blisters, which can be prevented by controlling them using complete personal protective equipment, falling from stairs can be prevented by routine inspection of the condition of the stairs, triggering fires in the combustion chamber can be prevented by providing training to oil pump operators, bumping heads can be prevented by wearing safety helmets, and Being crushed by goods can be prevented by neat arrangement of goods.